Does Social Innovation Require Social Entrepreneurship? - Asceline Groot; Ben Dankbaar (Technology Innovation Management Review, 2014)
Social innovation is now considered an important element in the search for solutions to pressing social problems. Inspired by Schumpeter’s conceptualization of innovation, "social" entrepreneurship is thought to contribute to "social" innovation in more or less the same way that "normal" entrepreneurship consists of the introduction of "normal" innovations. In the literature as well as in practice, the definition of concepts such as social innovation and social entrepreneurship has led to considerable confusion. We aim to bring clarity to the debate, arguing that every entrepreneurial action results in some measure of intended or unintended social innovation, regardless of whether the entrepreneurs in question are considered or consider themselves "social" or not. We test our insights in an investigation of 20 social enterprises that have a commercial business model.
Keywords: entrepreneurship; institutional change; Schumpeter; social change; social entrepreneurship; social innovation; sustainability